Medical English teaching and beyond: A multimodal and integrated approach - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Daniele Franceschi University of Pisa, Italy   ABSTRACT The aim of this paper is to show how Medical English teaching materials may be improved by introducing multimodal tasks encouraging a holistic approach to communication. Medical English for Specific Purposes textbooks and coursebooks typically focus on how to speak effectively, but they fail to prepare doctors to speak and behave affectively, although it has been demonstrated that how doctors communicate is as important as what they communicate in order to build a therapeutic alliance with their patients (Ambady et al. 2002; Cao et al. 2016; DiMatteo et al. 1980; Hall 1995, among others). Teaching materials should thus include activities aimed at strengthening doctors' ability to offer patient-centred care through mindful communication in association with specific body signals. A proof-of-concept teaching unit is provided here in order to exemplify how ESP materials could be made more responsive to the needs of professional practice by adopting a method that brings together targets for learning Medical English as well as counselling techniques.